Exploring NBT-6BT-2Zn cement composites for wastewater treatment: A Pyrocatalytic approach - Aditya Gaur; Nishchay Saurabh; Satyanarayan Patel (Results in Engineering)
In the present work, ceramic-cement composites are fabricated for wastewater treatment via pyrocatalysis. A 0.94Na0.5Bi0.5TiO3–0.06BaTiO3–2ZnO (NBT-6BT-2Zn) ceramics powder and cement are mixed in various ratios as 0:100, 30:70, 40:60, and 50:50 for pyrocatalysis-driven dye degradation. The fabricated ceramic-cement composites have several advantages compared to other composites as (i) they do not require a sintering step, which reduces the energy and cost of the fabrication process; (ii) they can be fabricated in any shape and size, and (iii) easy to incorporate in the actual application by coating on the surface which can act as pyrocatalyst. The composite samples are characterized structurally, electrically, and adsorption/desorption equilibrium. The NBT-6BT-2Zn: cement composites result in methylene blue (MB) dye degradation of 3.76 % (0:100), 10.83 % (30:70), 19.73 % (40:60), and 21.34 % (50:50) in 60 cycles. The MB dye degradation is further improved to ∼33 % in 60 heating/cooling cycles via coating the ceramics on the cement. The presence of O2•− and •OH radicals is confirmed using the scavenger and fluoresces test. The fabricated composites' reusability and repeatability tests are performed and provide consistent results. This work provides a new direction for using ceramic-cement composites as pyrocatalysis for water treatment.